Sacroiliitis Detected by Magnetic Resonance Imaging in Patients With Systemic Sclerosis - Didem ARSLAN; İpek TÜRK and Erkan KOZANOĞLU and Özlem KUDAŞ and Bayram KELLE and Hakan SAKALLI (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the magnetic resonance imaging (MRI) findings of sacroiliac joints in a selected group of patients with systemic sclerosis (SSc). Patients and methods: This retrospective study included 30 patients (2 males, 28 females; mean age 44.1±12.5 years; range, 24 to 70 years) with SSc who underwent MRI of sacroiliac joints. Lesions were defined according to Assessment of SpondyloArthritis International Society (ASAS)/Outcome Measures in Rheumatology MRI group criteria. Clinical features, conventional radiograms of sacroiliac joints, presence of inflammatory back pain, human leukocyte antigen B27 (HLA-B27), and C-reactive protein (CRP) levels were extracted from patient records. Results: Eleven of thirty patients (37%) revealed sacroiliitis on MRI (five with chronic, three with active sacroiliitis, and three with both active and chronic forms). On conventional radiographic examination, six patients had sacroiliitis (20%). In all of these six patients, sacroiliitis was also detected on MRI. CRP levels and number of patients with inflammatory back pain were found to be higher in the patients with active sacroiliitis (p<0.05). Seven patients were diagnosed as spondyloarthritis according to ASAS criteria. Conclusion: Sacroiliitis was detected more frequently by MRI compared to conventional radiographic examination. MRI is suggested to be the preferred method for evaluating sacroiliitis in SSc patients.